Penyuluhan Kesehatan Pemberian Tablet Zat Besi (Fe) Untuk Pembentukan Sel Darah Merah (Hb) Pada Masyarakat Pinggir Pantai Kelurahan Sumpang Binangae - Wijayanti, Lumastari Ajeng; Sumampouw, Oksfriani Jufri; Thalib, Kiki Uniatri; Cahyanta, Agung Nur; Abdullah, Rusli; Sabriana, Riska; Hikmah, Mutiara (Asosiasi Guru dan Dosen Seluruh Indonesia, 2024)
Iron is a mineral needed to form hemoglobin or red blood cells. Iron also plays a role in the formation of myoglobin (a protein that carries oxygen to muscles), collagen (a protein found in bones, cartilage and connective tissue), and enzymes. Iron can also be used for the body's defense system. The aim of this community service is to provide health education on the provision of iron (Fe) tablets for the formation of red blood cells (Hb) in the coastal community of Sumpang Binangae Subdistrict as many as 41 children. The Hb examination method used is analyzing children's capillary blood samples using the GCHb tool, then continuing with the distribution of vitamins. Meanwhile, the method of providing information regarding the importance of maintaining personal hygiene to parents of children is through oral presentations and joint discussions. The results of the Hb level examination obtained are compared with the standard reference for normal Hb values ​​and then analyzed whether the results are in accordance with normal values ​​or not. Meanwhile, from the results of the counseling, it was found that there was an increase in parents' understanding of the importance of children's health in increasing knowledge about the importance of children's health and providing children with vitamins was an effort to improve children's health for the sake of an intelligent generation.